THE INDUSTRIAL POTENTIAL OF THE SYRDARYA REGION AND ITS REPRESENTATION IN FINE ARTS (Web of Teachers: Inderscience Research, 2025)
This article explores the industrial potential of the Syrdarya region and its artistic representation in fine arts. By depicting factories, plants, power stations, and other industrial facilities, artists convey the value of human labor, the aesthetic dimension of technological progress, and the artistic interpretation of social development. The article also highlights the importance of industrial themes in the educational process for young artists and art students, emphasizing their harmony with local artistic traditions.